Does Toxoplasma gondii Infection Affect the Levels of IgE and Cytokines (IL-5, IL-6, IL-10, IL-12, and TNF-alpha)? - Joanna Matowicka-Karna; Violetta Dymicka-Piekarska; Halina Kemona (Clinical and Developmental Immunology)
In the study performed in a group of patients infected with T. gondii, we evaluated Th2 humoral response (IL-5, IL-6, IL-10) and Th1 cell response (IL-12, TNF-α). The study objective was to assess the effect of T. gondii on chosen indices of the immune response. The study involved 52 women infected with T. gondii (aged 18–42 years) prior to antiparasitic treatment. In all the patients, we found IgM (index >0.7) and IgG which exceeded 300 IU/ml. The control group (C) consisted of 40 healthy women aged 18–46 years. In the study group (T) and in the control group (C), the levels of IgE, IL-5, IL-6, IL-10, IL-12, and TNF-α were determined. In our study, T. gondii patients had twofold higher levels of IL-5 and IL-6 as compared to healthy subjects, which seems to confirm the presence of an inflammatory state. We found the level of IL-10 to be fivefold higher in the course of toxoplasmosis than in healthy controls. The levels of IL-12 and TNF-α were comparable to those observed in healthy controls. The study has revealed that that patients infected with T. gondii show increased production of the humoral response cytokines, whereas the generation of the cell response cytokines remains unchanged.